2014
DOI: 10.1007/s13105-014-0365-9
|View full text |Cite
|
Sign up to set email alerts
|

The role of casein in the development of hypercholesterolemia

Abstract: Atherosclerosis remains the leading cause of severe cardiovascular complications such as cardio- and cerebrovascular events. Given that prevention and early intervention play important roles in the reduction of cardiovascular complications associated with atherosclerosis, it is critical to better understand how to target the modifiable risk factors, such as diet, in order to best minimize their contributions to the development of the disease. Studies have shown that various dietary sources of protein can affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…However, whether or not this observed increase in risk is driven by protein per se is unclear and difficult to define. On the other hand, soy protein was claimed by the FDA (1999) to decrease cardiovascular disease risk through a cholesterol-lowering effect, whereas casein was thought to be hypercholesterolemic (10). In addition, given the current increased environmental impact of animal proteins, plant proteins are likely to be favored in the future for human consumption, given their lower environmental impact (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…However, whether or not this observed increase in risk is driven by protein per se is unclear and difficult to define. On the other hand, soy protein was claimed by the FDA (1999) to decrease cardiovascular disease risk through a cholesterol-lowering effect, whereas casein was thought to be hypercholesterolemic (10). In addition, given the current increased environmental impact of animal proteins, plant proteins are likely to be favored in the future for human consumption, given their lower environmental impact (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally these choices include increased fiber content which increase the absorption, and thus loss of bile acids through defecation [9]. This loss is compensated by increased hepatic modulation of plasma cholesterol into bile acids [15] with a subsequent reduction in serum cholesterol and thus a lower risk of CVD in vegans.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from randomized controlled trials (RCTs) indicated that milk protein supplementation was an effective diet approach for reducing blood pressure (BP) [ 8 , 9 ] specifically identifying casein as the most abundant high-quality protein in milk, which accounts for 80% of total milk protein [ 10 ]. Casein contains nearly all common amino acids and most essential amino acids [ 11 ]. It belongs to a slow-digesting protein, possessing a delayed release property in the digestive system.…”
Section: Introductionmentioning
confidence: 99%